PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN BATIK (Studi Pada Omah Batik Ngesti Pandowo, Semarang) - M. Arkan Zaky Khoiri; Handoyo DW (Jurnal Ilmu Administrasi Bisnis, 2018)
Creative industry especially in fashion sector have a high potential to boost Indonesian economy. One of the business sector of fashion industry in Indonesia is batik craft business.This research aims to know the influence of Product Quality, Service Quality, and Brand Image towards Buying Decision of Batik Product of Omah Batik Ngesti Pandowo.Sample in this research are 100 consumers who have purchased the product of Omah Batik Ngesti Pandowo. Data analysis that is used are validity test, reliability test, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, and test of significance ( t and F test) proceed by SPSS Program. The result of this research shows that product quality, service quality, and brand image have positive influence towards buying decision partially and simultantly. The conclusion for this research is the better Omah Batik Ngesti Pandowo’s product quality, service quality, and brand reputation are, the higher buying decision that is done by the consumers of Omah Batik Ngesti Pandowo.